Hydrogen sulfide and mitochondria - Gerush, I.V.; Ferenchuk, Ye.O. (Вiopolymers and Cell, 2019)
There are different opinions about the role of hydrogen sulfide (H2S) in catalytic and energy processes, but the biochemistry of all possible effects of H2S is not well studied yet. The enzymatic synthesis of H2S is catalyzed by cystathionine-γ-lyase, cystathionine-β-synthase, cysteine aminotransferase and in mitochondria by 3-mercaptopyruvate sulfurtransferase only. H2S may function as an energy substrate to sustain the ATP synthesis under stress conditions, but in high concentration H2S inhibits respiratory complex IV, blocking electron transport and proton pumping. The interaction between glucose in high concentrtaion, H2S, and the KATP channels may constitute a novel mechanism for the control of insulin secretion. The positive effect of H2S on the bioenergetic function of mitochondria may be used in therapy of many diseases. Існуть різні дані про роль гідроген судьфіду (H2S) в каталітичних та енергетичних процесах, але біохімічні механізми різноманітних ефектів H2S ще недостатньо вивчені. Ферментативний синтез H2S здійснюється цистатіонін-γ-ліазою, цистатіонін-β-синтазою, цистеїн амінотрансферазою, а в мітохондріях – 3-меркаптопіруват сульфуртрансферазою. H2S може функціонувати як енергетичний субстрат для підтримки синтезу АТФ в умовах стресу, але при високій концентрації молекула інгібує комплекс IV, блокуючи перенесення електронів. Взаємодія між високим рівнем глюкози, сірководнем і KATP-каналами може стати новим механізмом контролю секреції інсуліну, а ефект H2S на біоенергетичну функцію можна застосовувати при ускладненнях багатьох захворювань. Существуют различные данные о роли сероводорода (H2S) в каталитических и энергетических процессах организма, но биохимические механизмы всевозможных эффектов H2S еще недостаточно изучены. Ферментативный синтез H2S осуществляется цистатионин-γ-лиазой, цистатионин-β-синтазой, цистеин аминотрансферазой, а в митохондриях – 3-меркаптопируват сульфуртрансферазой. H2S может функционировать как энергетический субстрат для поддержания синтеза АТФ в условиях стресса, но в высокой концентрации молекула ингибирует комплекс IV, блокируя перенос электронов. Взаимодействие между высоким уровнем глюкозы, сероводородом и KATP-каналом может стать новым механизмом контроля секреции инсулина, а эффект H2S на биоэнергетическую функцию возможно применять при осложнениях многих заболеваний.